智歯抜歯を契機に発見された先天性血友病Bの1例 - 竹本, 隆; 阿知波, 基信 (日本口腔外科学会雑誌, 2014)
Hemophilia B is a disease in which the activity of blood coagulation factor IX (Christmas factor) decreases. A 22-year-old man was referred to our clinic by a local dental clinic. The medical and family history were irrelevant to the present disorder. The preoperative APTT value was 38.4 seconds, which was within normal limits. Four wisdom teeth had been extracted under intravenous sedation. On the first postoperative day, slight bleeding was observed from the left side of the upper jaw; this bleeding was controlled using an absorbable topical hemostat. The patient was discharged on the second day after surgery. However, repeated bleeding occurred from the fourth postoperative day, and the patient was re-hospitalized on the seventh day after surgery. The frequency of bleeding decreased gradually, and he was discharged from the hospital 12 days after surgery. The presence of a coagulation abnormality was suspected, and the patient was referred for hematological examination. He was given a diagnosis of hemophilia B based on the finding that the coagulation factor IX activity was reduced to 11%.